A new soft red winter wheat cultivar, 'GA 07353‐14E19', adapted to Georgia and the U.S. Southeast environments. Issue 2 (29th April 2021) - Mergoum, Mohamed; Johnson, Jerry W.; Buck, James W.; Sutton, Steve; Lopez, Benjamin; Bland, Daniel; Chen, Z.; Buntin, G. D.; Mailhot, Daniel J.; Babar, Md A.; Mason, Richard E.; Harrison, Stephen A.; et al.
Abstract: Soft red winter wheat (SRWW) ( Triticum aestivum L.), historically a major crop in Georgia and the U.S. Southeast (SE) region, has been challenged by numerous biotic and abiotic constraints resulting in decreased hectarage in recent years. Hence, an urgent need exists to release new cultivars with high yield potential, good resistance to predominant diseases and insects, and acceptable quality attributes to capture and maximize value in regional markets. The SRWW breeding program at the University of Georgia (UGA), in collaboration with the Southeastern University GRAINS (SUNGRAINS) breeding programs, is responding to these challenges by developing and releasing superior SRWW cultivars adapted to Georgia and the SE wheat region. 'GA 07353‐14E19' (Reg. no. CV‐1179, PI 689520), a SRWW cultivar developed by the UGA small grains breeding program, was released by the UGA College of Agricultural and Environmental Sciences and licensed to Stratton Seed Company in 2017 as GO WHEAT 2032. GA 07353‐14E19 is adapted to the SE region with high yield, good resistance to prevalent diseases, including leaf and stripe rusts, Fusarium head blight, powdery mildew, and Soil‐borne wheat mosaic virus . GA 07353‐14E19 also showed good resistance to current biotypes of Hessian fly. GA 07353‐14E19 possesses the H13, Sbm1, and Yr17 – Lr37 – Sr38 genes that protect it against the above pests. It has very good grain volume weight and good milling and baking quality as a SRWW.